Correlation between the designers' intention and the interpretation of the colors of a clothing collection by people of Generation Z - Dantas, Ítalo José de Medeiros (2022)
Fashion designers need to make conceptual-thematic choices, effectively delivering a message. Among the elements of visual language used in this codification, color, due to its symbolic aspect, plays an essencial role in the process of visual communication. Therefore, this article seeks to explore the interpretive possibilities of the semantic dimension of a color chart by comparing the effectiveness of the designers' intention on the visual message of colors in a clothing collection with the interpretation of potential Generation Z consumers. The semantic differential (SD) and the free word association (FWA) methods were used in this research, interviewing 4 designers, who coded the collection investigated in the scope of this work, and questioning 52 potential consumers of Generation Z. Thus, the results for SD and FWA suggested a moderate level of understanding between intention and interpretation of color messages.